Corporeal tales : an investigation into narrative form in contemporary South African dance and choreography - Parker, Alan Charles (Rhodes University, Faculty of Humanities, Department of Drama, 2008)
In the years following the fall of Apartheid in South Africa, dance and choreography have undergone considerable transformation. This investigation stems from one observation relative to this change that has been articulated by two of South Africa's most respected dance critics, Adrienne Sichel and Matthew Krouse. Both critics have noted a growing concern for narrative in South African contemporary choreography, coupled with an apparent propensity for narratives of a distinctly personal and 'autobiographical' nature. In Part One: 'Just after the beginning', the proposed preoccupation with narrative in South African contemporary choreography is discussed in light of the relationship between narrative and the notion of personal identity. The use of the performed narrative as a medium to explore questions about identity is offered as one explanation underpinning this increased proclivity, where the interrogation of the form of the danced narrative provides a site for exploration of personal identity. Part Two: 'Somewhere in the middle' interrogates the notion of form through an in-depth discussion of the experimentation with form within theatrical and antitheatrical dance traditions over the last fifty years. Specific works by three selected South African choreographers (Ginslov, Maqoma and Sabbagha) are discussed in terms of their general approach to narrative form. This provides an illustration of some of the approaches to narrative form emergent in contemporary South African choreographic practices. Part Three: 'Nearing the end' offers Acty Tang's Chaste (2007) as a case study to illustrate the practical application of the dance narrative as a means to interrogate questions relating to personal identity. A detailed analysis of Tang's particular approach to forming the narrative of Chaste is conducted, exposing the intertextual, multimedia and multidisciplinary approach to creating the danced narrative.
Keywords: Sichel, Adrienne; Krouse, Matthew; Dance -- South Africa; Choreography -- South Africa; Choreographers -- South Africa; Dance criticism -- South Africa